(3TQM GdJLQjO aj GdefWbs - (3MSf Hf eMeO Hf TQaTGg GdMSjfj GdCSJQGHGPis
(3ChdgG (B:s
(3CeG HYO MeO ddg GdhGLH GdhLhO dPGJg bhdg GdaUd GdChd ai eONd gPG GdYde s
(3BNQgG (B:s
(3CMOgG HfaS GdcdGe Ci GdcdGe GdeSJYed ajg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Hg Jedcs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdadSaI hGdefWbs